Effects of varying levels of sodium tripolyphosphate in beef patties - Solidum, Ma. Razcel Marquez
Effects of varying levels of sodium tripolyphosphate in the physico-chemical properties and sensory attributes of beef patties were studied. Selection of the best formulation from three hamburger recipes was first done. Selected formulation was used in the second phase where sodium trpolyphosphate (STP) was added at varying levels (0.0%, 0.2%, 0.35% and 0.5%). No significant relationship exists between all physico-chemical properties and STP concentration except for cooking loss. This maybe attributed to the manner of incorporation of STP. Water-holding (WHC), purge loss and cooking loss values had no significant difference as STP concentration was increased while pH had a significant difference between treatments at 5% level of significance. Panelists did not detect any significant difference in all the sensory attributes of the beef patties as STP concentration was increased.